Analisis Pengaruh Efektivitas Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) Terhadap Produktivitas Kerja Karyawan (Studi Kasus Plant 11 PT Indocement Tunggal Prakarsa, Tbk Citeureup) (Jurnal Manajemen dan Organisasi, 2016)
Employee is an important resource to have production process in a big factory. Factory couldn’t operate without employee. To protect their employees, the leader makes a policy like occupational health and safety. This policy for protect their employee from risk of bad accident and illness that causes of work. Bad accident can strike employee anywhere and anytime so this cases must to have a special attention. So, the leader, government, and management must pay attention to this risk.  Work accident leaning influence to manpower productivity because quality of work life and guarantee of occupational health and safety influence manpower productivity. PT Indocement Tunggal Prakarsa, Tbk is one of the biggest cement factories in Indonesia. This factory has applicated occupational health and safety assessment base on Permenaker No. 05/MEN/1996 and OHSAS 18001. Occupational health and safety effectiveness can describe by six aspect based on Miner Theory. That theory are safety training, safety publication, control to work environment, inspection and discipline, improvement awareness of occupational health and safety, report and statistic of occupational health and safety. Five aspect of Theory Miner, can describe by employee perspective, even report and statistic of occupational health and safety can describe by secondary data from Safety Department and Management Representative of PT ITP.